2020
DOI: 10.1002/we.2479
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous identification of wind turbine vibrations by using seismic data, elastic modeling and laser Doppler vibrometry

Abstract: This work compares continuous seismic ground motion recordings over several months on top of the foundation and in the near field of a wind turbine (WT) at Pfinztal, Germany, with numerical tower vibration simulations and simultaneous optical measurements. We are able to distinguish between the excitation of eigenfrequencies of the tower‐nacelle system and the influence of the blade rotation on seismic data by analyzing different wind and turbine conditions. We can allocate most of the major spectral peaks to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The observed WT-induced frequency peaks in this study agree with previously identified frequency peaks in the vicinity of nearby wind farms (e.g. Styles et al, 2005;Stammler and Ceranna, 2016;Flores Estrella et al, 2017;Zieger and Ritter, 2018;Neuffer et al, 2019) and specifically at Pfinztal (Zieger et al, 2020).…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 92%
See 1 more Smart Citation
“…The observed WT-induced frequency peaks in this study agree with previously identified frequency peaks in the vicinity of nearby wind farms (e.g. Styles et al, 2005;Stammler and Ceranna, 2016;Flores Estrella et al, 2017;Zieger and Ritter, 2018;Neuffer et al, 2019) and specifically at Pfinztal (Zieger et al, 2020).…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 92%
“…The WT is located at the Fraunhofer Institute for Chemical Technology in Pfinztal, Germany, about 8 km northeast of the city of Karlsruhe. A previous study demonstrated that ground motion emissions correlate with structural properties of the WT in Pfinztal (Zieger et al, 2020). We installed 20 MARK L-4C-3D geophones with an eigenfrequency of 1 Hz (Fig.…”
Section: S E T T I N Gmentioning
confidence: 99%
“…The results also show that crucial dynamic features of the system, such as eigenfrequencies and mode shapes, can be precisely derived from the analysis results. In another study, LDV measurements were carried out on wind turbines to distinguish different operating conditions, and a simulation was made to validate the results of this study [17]. Then, spectral peaks that correspond to the blade eigenfrequencies, bladepassing frequency, and tower bending modes were identified.…”
Section: Introductionmentioning
confidence: 99%
“…If the object is moving, this creates a wavelength and phase difference between the sent and the received laser beams. By using the Doppler principle, the velocity or displacement of the object can be calculated with very high accuracy (in mm range) from distances up to 300-400 m [9][10][11].…”
Section: Introductionmentioning
confidence: 99%